PARTICIPATORY APPROACH FOR THE EVALUATION OF THE TYPE OF PROTECTION OF MARITIME HERITAGE IN URBAN REGENERATION PROJECTS OF WATERFRONTS - CASE OF THE PORT OF ALGIERS - Nour El Houda Bouchefirat,; Djamel Dekoumi, (International Journal of Innovative Technologies in Social Science, 2024)
Coastlines are closely linked to the development of civilizations, as essential places for anchoring commercial and military activities, and for innovation in the forms and techniques of appropriation of the sea, which has produced throughout history a stratification of maritime heritage in the coastal area, today threatened with degradation and disappearance mainly due to natural and climatic conditions and the accelerated urbanization of the coastline, at a time when this heritage can constitute a powerful lever for revitalizing the waterfronts. The historic port of Algiers, the subject of this research, bears witness to a great historical and typological wealth in terms of maritime heritage. Being an integral part of the major regeneration project of the Bay of Algiers, major socio-cultural and economic issues are linked to the choice of the degree of protection of the site's buildings. The objective of this research is to propose a participatory and sustainable approach for the classification of maritime legacies according to their type of protection in the urban regeneration process of the waterfront of the Bay of Algiers, in order to identify development strategies that respect both the spirit of the place and allow the social and economic development of the urban space. To achieve the objective, the Delphi method. This made it possible to structure the evaluation tool and weight the criteria. The established tool is composed of 24 criteria classified according to 5 aspects; architectural quality, historical interest, social role, economic impact and state of conservation. The approach chosen in this study has the advantage of being global, transferable and adaptable to similar decision-making contexts.